Suprarealismul sau literatura abisurilor - Mihaela Paula GALU (ACROSS)
Surrealism, the last movement of the historical avant-garde, is tackled in this paper firstly from a general standpoint, including a brief history of what it signified at the world level, narrowing then down on the local occurrences, divided into two stages: before and after 1940. Telling for the aims of this paper is Gellu Naum’s statement: “I bear in me the profound sadness of poets who have struggled their entire life not to make literature and, in the end, after having skimmed through more than one hundred pages, realized that they made nothing but literature.” This is a resigned outcry of a generation: wishing (and attempting to accomplish) the death of literature, avant-garde writers, and especially Surrealists, only managed to give it extra life and vitality through their revolted writings.